Studies of charm and beauty hadron long-range correlations in pp and pPb collisions at LHC energies - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Bergauer,T; Dragicevic,M; Ero,J; Del,Valle AE; Flechl,M; Fruhwirth,R; Jeitler,M; Krammer,N; et al. (Physics Letters B: Nuclear Physics and Particle Physics, 2021)
Measurements of the second Fourier harmonic coefficient (v2) of the azimuthal distributions of promptand nonprompt D0 mesons produced in pp and pPb collisions are presented. Nonprompt D0 mesons comefrom beauty hadron decays. The data samples are collected by the CMS experiment at nucleon-nucleoncenter-of-mass energies of 13 and 8.16 TeV, respectively. In high multiplicity pp collisions, v2 signalsfor prompt charm hadrons are reported for the first time, and are found to be comparable to those forlight-flavor hadron species over a transverse momentum (pT) range of 2–6 GeV. Compared at similarevent multiplicities, the prompt D0 meson v2 values in pp and pPb collisions are similar in magnitude.The v2 values for open beauty hadrons are extracted for the first time via nonprompt D0 mesons inpPb collisions. For pT in the range of 2–5 GeV, the results suggest that v2 for nonprompt D0 mesons issmaller than that for prompt D0 mesons. These new measurements indicate a positive charm hadron v2in pp collisions and suggest a mass dependence in v2 between charm and beauty hadrons in the pPbsystem. These results provide insights into the origin of heavy-flavor quark collectivity in small systems